Effect of biosurfactant on hydrolysis of municipal waste by cellulases producing bacteria for bioethanol production - Mohamed Hosny; Huda S. El-Sheshtawy (Current Research in Green and Sustainable Chemistry, 2022)
The present study deals with the disposal of MW in an eco-friendly manner to the environment and the production of valuable products from cheap waste. From the MW sample, fifteen bacterial isolates (B1–B15) have been isolated. The screening for the biological hydrolysis of MW by cellulases producing bacteria and total reducing sugar production (TRS) was studied. Bacterial isolates B1, B2, B3, B6, B7, and B10 were selected for their ability to hydrolyse MW and TRS production. The highest (TRS) were at 8528.1, 7636.1, 7189.8, 7152.9, 6564.1, and 6539.4 ​μg/mL produced by bacterial isolates B10, B2, B7, B6, B1 and B3 respectively. Carboxy methyl cellulase (CMCase), filter paperase (FPase), and avicelase production were studied. Bacterial isolate (B10) has the highest levels of CMCase (1576.5 U/mL), FPase (1421.4 U/mL), and Avicellase (2080.3 U/mL). Each selected bacterial isolate was tested for the production of biosurfactants. The highest drop displacement test and emulsification power, at 30 ​mm and 97%, respectively, were obtained from the biosurfactant. The isolate (B10) was identified as Bacillus subtilis DSM15029 by 16S rRNA. The effect of chemical and bio-surfactants on MW hydrolysis and cellulolytic enzyme production was carried out. The highest TRS, 9076.1 and 8367.6 ​μg/mL was observed using biosurfactant and Tween-80, respectively. The highest CMCase, FPase, and Avicellase activities (1643.5, 1590.73, and 2113.69 U/mL) were recorded with a biosurfactant. The batch fermentation of MW hydrolysate was performed with a biosurfactant. The highest bioethanol production (60.27 ​mL/L) was recorded after 72 ​h using GC analysis.